Elements in Mediterranean mussels from Istanbul and exposure assessment - Turkoglu, Semra; Kaya, Gokce; Yaman, Mehmet (Taylor & Francis Ltd, 2023)
In this study, concentrations of elements were determined in edible tissues of Mytilus galloprovincialis by means of inductively coupled plasma mass spectrometry (ICP-MS). The mean levels (mg kg(-1)) of 0.67 for Cd, 6.9 for As, 0.79 for Pb, 2 for Ni, and 42.6 for Zn exceeded the maximum limits in the digestive glands. Also, the mean concentrations of Cd and As in muscle and of Cd and Ni in gills were above the maximum limits. The highest value was found for As in a digestive gland, with 65.4% of the Provisional Tolerable Weekly Intake. In addition, the lowest percentage belonged to Zn with 0.2% of PTWI in muscles and 0.3% of PTWI in gills of the mussels. Mercury concentrations were well below legal limits.
Keywords: Mytilus galloprovincialis; elements; bioindicator; heavy metals; ICP-MS; mussels